2008
DOI: 10.15288/jsad.2008.69.275
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Adolescent Alcohol Involvement as Predictors of Young-Adult Major Depression

Abstract: Objective-Adolescent alcohol involvement may increase risk for young-adult depression; however, findings are mixed and important questions remain unanswered. Because alcohol involvement among teens is multidimensional, this study examined the extent to which four different adolescent alcohol dimensions (i.e., frequency of alcohol use, quantity of consumption, frequency of heavy episodic drinking, and frequency of problem use) were predictive of young-adult major depressive disorder (MDD).Method-Participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 62 publications
2
55
2
3
Order By: Relevance
“…Alcohol use is multi-dimensional [23][24][25], and each measure of use captures a distinct aspect of consumption. Frequency measures assess exposure to alcohol but neglect the importance of quantity consumed per occasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol use is multi-dimensional [23][24][25], and each measure of use captures a distinct aspect of consumption. Frequency measures assess exposure to alcohol but neglect the importance of quantity consumed per occasion.…”
Section: Introductionmentioning
confidence: 99%
“…Although alcohol indices are highly correlated at a single time-point [24,[29][30][31], longitudinal research suggests that indices may change differentially over time and are differentially related to health outcomes [12,[32][33][34][35][36][37][38][39][40]. Following 714 emerging adults (ages 18-26), Casswell, Pledger & Pratap [12] found that typical quantity peaked at age 21 and then declined, whereas drinking frequency continued to increase steadily over time.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most studies have focused on the relationship between clinical levels of internalizing and alcohol problems (Boschloo et al, 2011;Dawson et al, 2010;Grant et al, 2004;Schneier et al, 2010); the relationship between nonclinical alcohol phenotypes and later clinical levels of internalizing problems has been less well characterized, although it has been the focus of some research (e.g., Mason et al, 2008;Needham, 2007;Rohde et al, 1996;Weitzman, 2004). Such information has important public health consequences: If normative drinking is predictive of later internalizing problems, education and prevention efforts should not be limited to the most severely affected adolescent drinkers (Rose, 2001).…”
mentioning
confidence: 99%
“…By contrast, Repetto et al (2004) reported that higher depression in high school predicted greater future alcohol use in boys but not girls. Reminding us again that amount of substance use is not synonymous with problems caused by the use, Mason et al (2008) reported that after controlling for gender and depressed mood, alcohol problems but not amount of alcohol use predicted later major depressive episodes in adolescents. Also reminding us that stressful experiences are not synonymous with stressful reactions to those situations, Wu et al (2010) reported that alcohol use initiation was more common within 2 years of a trauma in 10-to 13-year-olds, but only among those who developed signifi cant symptoms of posttraumatic stress disorder.…”
Section: Modern Longitudinal Studies Of Comorbiditymentioning
confidence: 91%